2021
DOI: 10.3390/cells10102550
|View full text |Cite
|
Sign up to set email alerts
|

Caspase-Dependent HMGB1 Release from Macrophages Participates in Peripheral Neuropathy Caused by Bortezomib, a Proteasome-Inhibiting Chemotherapeutic Agent, in Mice

Abstract: Given the role of macrophage-derived high mobility group box 1 (HMGB1) in chemotherapy-induced peripheral neuropathy (CIPN) caused by paclitaxel, we analyzed the role of HMGB1 and macrophages in the CIPN caused by bortezomib, a proteasome-inhibiting chemotherapeutic agent used for the treatment of multiple myeloma. Repeated administration of bortezomib caused CIPN accompanied by early-stage macrophage accumulation in the dorsal root ganglion. This CIPN was prevented by an anti-HMGB1-neutralizing antibody, thro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 36 publications
1
4
0
Order By: Relevance
“…Notably our finding of caspase-dependent HMGB1 release is consistent with results in e.g. apoptosis-mediated sepsis (42) and for macrophages treated with a proteasome inhibitor (43). Furthermore, our results suggest that caspase inhibition does not always abolish the HMGB1 release, as shown for H1975 cells where the caspase inhibition also caused phosphorylation of MLKL, a necroptosis marker.…”
Section: Discussionsupporting
confidence: 91%
“…Notably our finding of caspase-dependent HMGB1 release is consistent with results in e.g. apoptosis-mediated sepsis (42) and for macrophages treated with a proteasome inhibitor (43). Furthermore, our results suggest that caspase inhibition does not always abolish the HMGB1 release, as shown for H1975 cells where the caspase inhibition also caused phosphorylation of MLKL, a necroptosis marker.…”
Section: Discussionsupporting
confidence: 91%
“…A recent placebo-controlled, double-blind, randomized study indicates that recombinant thrombomodulin, which directly binds to HMGB1 and improves its degradation by thrombin, has a preventive effect against oxaliplatin-induced PN (Kotaka et al, 2020). Two preclinical studies also found that recombinant thrombomodulin could prevent peripheral neuropathy induced by bortezomib and paclitaxel in rats and mice (Miyamoto et al, 2021;Tsubota et al, 2021). Tsubota et al indicated that anticoagulant (argatroban) could promote bortezomib-induced peripheral neuropathy (BIPN) and cancel the anti-BIPN effect of recombinant thrombomodulin (Tsubota et al, 2021).…”
Section: Discussionmentioning
confidence: 99%
“…Two preclinical studies also found that recombinant thrombomodulin could prevent peripheral neuropathy induced by bortezomib and paclitaxel in rats and mice (Miyamoto et al, 2021;Tsubota et al, 2021). Tsubota et al indicated that anticoagulant (argatroban) could promote bortezomib-induced peripheral neuropathy (BIPN) and cancel the anti-BIPN effect of recombinant thrombomodulin (Tsubota et al, 2021). The impact of anticoagulants on PN was dose dependent.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In severe cases, dosage reduction or discontinuation of chemotherapy may be necessary. In recent years, numerous studies have investigated the pharmacological effects of HMGB1 on tumor pain and neuralgia, given its strong pro-inflammatory and propain activities ( 82 84 ). Studies have shown that an anti-HMGB1-neutralizing antibody can effectively inhibit CIPN in animals receiving chemotherapy ( 85 ).…”
Section: Role Of Hmgb1 In Immunotherapymentioning
confidence: 99%